Sympathetic activation: a potential link between comorbidities and COVID‐19. (1st August 2020) - Porzionato, Andrea; Emmi, Aron; Barbon, Silvia; Boscolo‐Berto, Rafael; Stecco, Carla; Stocco, Elena; Macchi, Veronica; De Caro, Raffaele
Abstract : In coronavirus disease 2019 (COVID‐19), higher morbidity and mortality are associated with age, male gender, and comorbidities, such as chronic lung diseases, cardiovascular pathologies, hypertension, kidney diseases, diabetes mellitus, and obesity. All of the above conditions are characterized by increased sympathetic discharge, which may exert significant detrimental effects on COVID‐19 patients, through actions on the lungs, heart, blood vessels, kidneys, metabolism, and/or immune system. Furthermore, COVID‐19 may also increase sympathetic discharge, through changes in blood gases (chronic intermittent hypoxia, hyperpnea), angiotensin‐converting enzyme (ACE)1/ACE2 imbalance, immune/inflammatory factors, or emotional distress. Nevertheless, the potential role of the sympathetic nervous system has not yet been considered in the pathophysiology of COVID‐19. In our opinion, sympathetic overactivation could represent a so‐far undervalued mechanism for a vicious circle between COVID‐19 and comorbidities. Abstract : Aging and comorbidities (lung, cardiovascular, kidney, and metabolic diseases) are characterized by sympathetic overactivity, which may exert detrimental effects on lungs, heart, vessels, kidney, metabolism, and/or immune system of coronavirus disease 2019 (COVID‐19) patients. COVID‐19 may furtherly increase sympathetic discharge, through hypoxia, angiotensin‐converting enzyme (ACE)1/ACE2 imbalance, immune/inflammatory factors, and emotional distress. Thus, sympathetic activation could represent a so‐far undervalued mechanism for a vicious circle between COVID‐19 and comorbidities.